2009
DOI: 10.3109/09540260903340865
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of burn injuries: Highlighting cultural and socio-demographic aspects

Abstract: Burns are devastating injuries that disproportionately affect people in developing countries, including children. In addition to a high mortality rate, survivors are burdened with life-long physical and emotional scars. The etiology and nature of burn injuries varies significantly by country, and this chapter explores the predominant causes and patterns of burn injury in both the developing and industrialized worlds. Gender differences play a significant role in the risk of burn injuries, across a spectrum wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
73
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(86 citation statements)
references
References 87 publications
9
73
1
1
Order By: Relevance
“…Most burn occurred from natural gas, gasoline and kerosene (51.7%), followed by open fire (10.2%). In this regard, our findings were not consistent with those of other studies, which identified open fire as the main cause [1,3,13,15]. This discrepancy could be partly explained by the nature of reported burn differences, such as use of unsafe equipment in the workplace or at home, mishandling of gasoline or kerosene in gas stations, and use of kerosene as a main source for home heat by low income families.…”
Section: Settingscontrasting
confidence: 57%
See 2 more Smart Citations
“…Most burn occurred from natural gas, gasoline and kerosene (51.7%), followed by open fire (10.2%). In this regard, our findings were not consistent with those of other studies, which identified open fire as the main cause [1,3,13,15]. This discrepancy could be partly explained by the nature of reported burn differences, such as use of unsafe equipment in the workplace or at home, mishandling of gasoline or kerosene in gas stations, and use of kerosene as a main source for home heat by low income families.…”
Section: Settingscontrasting
confidence: 57%
“…This could be reduced by effective prevention plans based on the identification of major risk groups (of sex and age) and on safety pitfalls [1]. In Iran, these data have been systematically collected and analyzed, but plans and follow-up did not reach the proposed goals.…”
Section: Brief Communication (Original)mentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Burns from hot drinks, food, steam, or other hot liquids are common causes of burn injuries to young children compared to other burn injuries. 2 Burn patients are at high risk for infection as a result of the nature of the burn injury itself, the immunocompromizing effects of burns, prolonged hospital stays, and intensive diagnostic and therapeutic procedures. Sepsis of burn wounds is a serious problem leading to death and is one of the most important factors determining the prognosis of burn disease.…”
Section: Introductionmentioning
confidence: 99%
“…Burn is a major cause of morbidity and mortality, and it is the fourth most common type of trauma worldwide. 1,2 Burn is a major issue on public health in terms of infection control and cost of treatment in both developing and developed countries, and burn in pediatric range from minor to severe injuries 3 Injuries in pediatrics are predictable, avoidable and preventable. 4,5 Burns from hot drinks, food, steam, or other hot liquids are common causes of burn injuries to young children compared to other burn injuries.…”
Section: Introductionmentioning
confidence: 99%